Konstruksi Pemikiran Filosofis JasserAuda: Analisis Epistemologis terhadap Pembaruan Maqasid al-Syari‘ah Kontemporer - Putra, Muh.; Sultan, Lomba; HL, Rahmatiah (Mazalat: Jurnal Pemikiran Islam, 2026)
Jasser Auda is a contemporary thinker (philosopher) who introduced the concept of Maqasid al-Shari'ah as a response to his dissatisfaction with traditional Usul al-Fiqh. One of the concerns he felt was that Usul al Fiqh tended to be textual and often overlooked the purpose of the text. This literal and textual reading arose from the excessive attention of Usul al Fiqh scholars to the linguistic aspect. Therefore, to facilitate the research, the researcher used library research to obtain some data and information related to this study. The data was taken from several sources such as books, journals, online media, and others. From this research, Jasser Auda ultimately emphasizes that the Maqashid of Islamic law are the fundamental goals of all ijtihad methodologies, whether based on linguistic or rational Usul. Furthermore, achieving Maqashid, from a system perspective, supports the principles of openness, innovation, realism, and flexibility in Islamic law.